Characterizations of m-EP elements in rings. Issue 6 (3rd June 2018) - Zou, Honglin; Chen, Jianlong; Patrício, Pedro
Abstract: Let R be a ring with involution. In this paper, we extend the notions of m -EP matrices and m -EP operators to an arbitrary ring case. A number of new characterizations of m -EP elements in rings are presented. In particular, the existence criteria for 1-EP (i.e. EP) elements are obtained by means of the group inverse, Moore–Penrose inverse, and core inverse. Some properties of 2-EP are also given.